A new species of Criocerinae (Chrysomelidae) from New Caledonia: Oulema (Oulema) taophiloides sp. nov. - Gómez-Zurita, Jesús (Zootaxa, 2011)
The first New Caledonian record for the genus Oulema Des Gozis (Coleoptera: Chrysomelidae) is reported here with the description of a new species: Oulema taophiloides sp. nov.